The relationship between food product with the JAKIM halal certification and performance of certified halal food manufacturers - Abu Karim, Rizuwan; Mohd Nawi, Nolila; Abd Razak, Noraznira; Marmaya, Najihah Hanisah; Ridzuan, Abdul Rauf (Human Resource Management Academic Research Society, 2018)
Due to the continuous demand and the importance of Shariah compliance of halal food to the Muslims consumers, this study examined the impact of trust and safety of food product with the JAKIM halal certification towards performance of food manufacturers. The structural equation modeling techniques (SEM) was used to examine the relationship between trust, safety and performance of food manufacturers. Data was analyzed through partial least square structural equation modelling (PLS - SEM). Meanwhile, WARP PLS version 5.0 were used for the statistical processing of the data in this study. The findings suggested that trust significantly and positively influence performance of food manufacturers. In addition, safety also were found to have positive and significant relationship with performance of food manufacturers.